2015
DOI: 10.1371/journal.pone.0125728
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Tumor-Associated Macrophages According to Histologic Locations and Hormone Receptor Status in Breast Cancer

Abstract: Tumor-associated macrophages (TAMs) are involved in tumor progression by promoting epithelial-mesenchymal transition (EMT), tumor cell invasion, migration and angiogenesis. However, in breast cancer, the clinical relevance of the TAM infiltration according to distinct histologic locations (intratumoral vs. stromal) and hormone receptor status is unclear. We investigated the significance of the levels of TAM infiltration in distinct histologic locations in invasive breast cancer. We also examined the relationsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
84
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(108 citation statements)
references
References 32 publications
12
84
0
2
Order By: Relevance
“…Inflammatory markers have been elevated in studies of hormone negative cancers. (6567) RNASEL variants have been associated with elevated inflammatory biomarkers(68) and the enzyme encoded by the RNASEL gene has proinflammatory functions. (69)…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory markers have been elevated in studies of hormone negative cancers. (6567) RNASEL variants have been associated with elevated inflammatory biomarkers(68) and the enzyme encoded by the RNASEL gene has proinflammatory functions. (69)…”
Section: Discussionmentioning
confidence: 99%
“…TAMs may also promote tumor growth, as a high density of TAMs seems to be associated with increased mortality in patients with gastric, urogenital and mammary cancer, and OSCC (7,8).…”
mentioning
confidence: 99%
“…While it has been observed that macrophage infiltration occurs to a lesser extent in luminal A versus other tumor subtypes, 44 interactions between cancer cells and macrophages have not been assessed. We utilize MCF7 (luminal A), SKBR3 (HER2+), and MDA-MB-231 (triple negative, claudin-low) cell lines in concert with RAW 264.7 macrophages at approximately a 2:1 ratio.…”
Section: Resultsmentioning
confidence: 99%